A Review of the Risk Factors for Iron Deficiency Anaemia among Adolescents in Developing Countries. (3rd January 2023) - Wiafe, Michael Akenteng; Ayenu, Jessica; Eli-Cophie, Divine
Abstract : Introduction . Identifying the root causes of iron deficiency anaemia is a prerequisite for effective management and prevention in adolescents. This systematic review assessed risk factors of iron deficiency anaemia among adolescents living in developing countries. Method . Electronic databases such as PubMed, Cochrane Library, Science Direct, Google Scholar, and SCOPUS were comprehensively searched for studies published between 1990 and 2020 that involved risk factors of iron deficiency anaemia among adolescents living in developing countries. The quality of the included studies was assessed using the American Dietetic Association Quality Criteria Checklist. Results . A total of 2, 252 publications were reviewed, and only fifteen cross-sectional studies were eligible for inclusion, eight of which focused on female adolescents and seven on both genders. Direct risk factors contributing to anaemia among adolescents included food intake practices ( n = 10 studies), female adolescents ( n = 8 studies), menstruation ( n = 5 studies), and parasitic infection ( n = 6 studies). Indirect risk factors found to be associated with anaemia among adolescents included low educational status ( n = 4 studies) and low socioeconomic status ( n = 3 studies). All fifteen studies were of good quality. Conclusion . Food intake practices, female adolescents, menstruation, parasitic infection, and low educational status were the leading risk factors of iron deficiency anaemia among adolescents. Further research should concentrate on assessing the effectiveness and efficacy of existing interventions aimed at preventing iron deficiency among vulnerable groups in developing countries.